PERSONIFICATION: HOW IS THE FIGURE OF SPEECH POSITIONED? - Ugi Sutikno, Eka (JEDLISH : Journal Of Education and English Language Teaching, 2025)
Personification to distinguish between what is human and what is not. However, the most common is personification, which involves humanising objects, animals, and abstract concepts. The purpose of discussing five poems from “Selamat Ulang Tahun, Buku” by Joko Pinurbo, “Hiu” by Nirwan Dewanto, “Because I could not stop for Death” by Emily Dickinson, “The Mangroves” by Mary Oliver, and “Laughing Song” by William Blake which have personification. The method used in this article is a qualitative descriptive approach. The results obtained are that the five poems above have human nature embedded in the form of objects (such as ‘buku,’ ‘streams,’ and ‘hills’), animals (such as ‘hiu,’ ‘ubur-ubur,’ ‘cumi-cumi,’ ‘grasshopper,’ and ‘birds’), abstract (such as death), plants (such as ‘mangroves,’ ‘green woods,’ and ‘meadow’), and gas (such as ‘air’). The five forms above are examples of personification. So the conclusion is that in Joko Pinurbo's poem, there are objects that behave like humans; in Nirwan Dewanto's poem, human nature is linked to three animals; in Emily Dickinson’s poem, it is said that Death has a quiet, honest, and cruel behavioural action; in Mary Oliver's poem it is said that mangroves have the nature to discuss with the narrator; William Blake gives the nature of happiness to objects and animals. Thus, personification functions as a complement to characteristics, emotions, and position as a story character.